The influence of leadership style on employee job satisfaction in Terengganu State Economic Development Corporation (TSEDC): the moderating effect of organizational support / Suhaili Mohd Nor - Mohd Nor, Suhaili (2014)
The issues of leadership style and job satisfaction is a topic that had been explored by many researchers. The result of relationship between leadership style and employees satisfaction may be vary from one organization to another due to nature of work, working experience, organizational culture or age. Therefore, this study is carried out as an attempt to highlight the relationship between leadership style and job satisfaction among employees at Terengganu State Economic Development Corporation (TSEDC). In order to identify the relationship between leadership style, job satisfaction and organizational support as moderator, 140 set of questionnaire has been distributed at TSEDC. Based on the objectives and research questions developed, the findings show that the leadership style have significantly impact job satisfaction. Furthermore, based on the findings of hierarchical regression analysis, it was found that organizational support do not moderate the relationship between leadership styles and job satisfaction among employees at TSEDC. Therefore, hopefully the result can be valued and can be used as reference to any organization or individual to develop the leadership style favorable by employees but it should depend on situation.